2019
DOI: 10.1021/acs.molpharmaceut.9b01109
|View full text |Cite
|
Sign up to set email alerts
|

Formulating Amorphous Solid Dispersions: Impact of Inorganic Salts on Drug Release from Tablets Containing Itraconazole-HPMC Extrudate

Abstract: Amorphous solid dispersions (ASD) are increasingly used to improve the oral bioavailability of poorly water-soluble compounds. However, hydrophilic polymers in ASD have high water-binding properties and, upon water contact, they often form a gel on the surface of the tablet, impacting the rate and extent of drug release. Most inorganic salts decrease water solubility of organic solutes, changing the gel properties of hydrophilic polymers. In this study, the effect of inorganic salts on drug release from a tabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…Identifying the critical process parameters (CPPs) and critical quality attributes of materials (CMAs) impacting the CQAs of the product is the next step. CPPs are "process parameter whose variability has an impact on a critical quality attribute of the product and therefore should be monitored or controlled to ensure the process produces the desired quality" [24]. The CPPs for each unit operation (filling, pre-compression, main compression, de-compression and ejection) during the direct compression process must be considered (Figure 2).…”
Section: Identification Of Cqas Cmas and Cpps Of The Tableting Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying the critical process parameters (CPPs) and critical quality attributes of materials (CMAs) impacting the CQAs of the product is the next step. CPPs are "process parameter whose variability has an impact on a critical quality attribute of the product and therefore should be monitored or controlled to ensure the process produces the desired quality" [24]. The CPPs for each unit operation (filling, pre-compression, main compression, de-compression and ejection) during the direct compression process must be considered (Figure 2).…”
Section: Identification Of Cqas Cmas and Cpps Of The Tableting Processmentioning
confidence: 99%
“…Previous studies have also explored the use of inorganic salts with hydroxypropyl methyl cellulose (HPMC) and Soluplus ® with various drugs and have found enhanced dissolution rate of the ASDs [20][21][22][23]. Takano et al [24] also reported that tablets of ITZ ASD and potassium salts (KCl, KH 2 PO 4 , KHCO 3 ) had a faster drug release compared to tablets without salts during dissolution. These are known to be kosmotropic salts, which are thought to compete for water hydration near the polymer chain, hence, preventing polymer gelation and, therefore, facilitating disintegration and dissolution [25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the difference in the performance of suspensions and solid dosage forms has been increasingly observed recently. The most typical approach to fill this gap is to improve the dissolution behavior of ASDs using additives such as inorganic salts [21,22].…”
Section: Relationship Between Dissolution Behavior and Oral Absorptionmentioning
confidence: 99%
“…The recent research found by HPMC polymers are reported. [8][9][10][11][12][13][14] The HPMC K100LV or K4M slows the release of the medication by 4 or 8 hr, respectively. The HPMC K100M was preferred for a sustained-released period of more than 12 hr, and the percentage of HPMC K100M in formulations grew to 41%.…”
Section: Introductionmentioning
confidence: 99%